The claiming - Warga, Jasmine (Last resort (Scholastic Press), 2026)
For the first time, Teddy is actually excited for the school year to start. His new neighbors, Lila and Caleb, are transferring to his school, which means he'll finally have real friends! But Teddy has a secret he's desperate to protect--one that explains why none of his classmates have spoken to him in years... And that's not all. Despite having sent the fire maiden back through the portal, strange things keep happening at the Castle Hill Inn. Teddy's nightmares are back in a big way, and after getting stuck in the portal herself, Lila seems to be... flickering?! Almost as if something, or someone, is trying to summon her from our world into the next. Teddy will do anything to protect his friends, but he's terrified of repeating the worst mistake of his life. Yet Teddy might be the key to uncovering the fire maiden's evil plans, and in order to stop her, he'll have to face his greatest fears--the ones he's spent his whole life running from.